Catalytic performance of Metal-Organic-Frameworks vs. extra-large pore zeolite UTL in condensation reactions - Shamzhy, Mariya; Opanasenko, Maksym; Shvets, Oleksiy; Čejka, Jiří (Frontiers in Chemistry, 2013)
Catalytic behavior of isomorphously substituted B‐, Al‐, Ga‐, and Fe‐containing extra‐large pore UTL zeolites was investigated in Knoevenagel condensation involving aldehydes, Pechmann condensation of 1‐naphthol with ethylacetoacetate, and Prins reaction of β‐pinene with formaldehyde and compared with large‐pore aluminosilicate zeolite BEA and representative Metal‐Organic‐Frameworks Cu3(BTC)2 and Fe(BTC). The yield of the target product over the investigated catalysts in Knoevenagel condensation increases in the following sequence: (Al)BEA < (Al)UTL < (Ga)UTL < (Fe)UTL < Fe(BTC) < (B)UTL < Cu3(BTC)2 being mainly related to the improving selectivity with decreasing strength of active sites of the individual catalysts. The catalytic performance of Fe(BTC), containing the highest concentration of Lewis acid sites of the appropriate strength is superior over large‐pore zeolite (Al)BEA and B‐, Al‐, Ga‐, Fe‐substituted extra‐large pore zeolites UTL in Prins reaction of β‐pinene with formaldehyde and Pechmann condensation of 1‐naphthol with ethylacetoacetate.